Moderating Effect of Work Place Support on the Social Life of Night Shift Employees - James, Fabian; Sudha, S. (Prabandhan: Indian Journal of Management, 2017)
The main purpose of this paper was to examine the moderating effect of workplace support on the social life of night shift employees working in the logistics industry. We aimed to find whether workplace support as a moderator had an effect on the relationship of night shift hassles and social life as well as night shift hours and social life. We used night shift hassles and night shift hours as the exogenous variables and social life as the endogenous variable. We used workplace support as the moderator to find if workplace support influenced the relationship between night shift hassles and social life as well as night shift hours and social life. Multiple step by step regression method was also used to find the relationship between night shift hassles and social life as well as night shift hours and social life. We then computed the interaction variable to find its influence on the relationship between exogenous variables (night shift hassles & night shift hours) and social life. The findings suggested that the interaction variable had a significant effect and influenced the relationship between the exogenous variables and the endogenous variable.